The Effect of Leadership and Knowledge Management on Employee Performance with Learning Organization As An Intervening Variable (Case Study at The Inda Deputy for The Corruption Eradication Commission Republic of Indonesia– KPK RI) - Bagoes Purnomo; M. Ali Iqba (Indonesian Journal of Business Analytics, 2023)
This study aims to analyze the effect of transformational leadership and knowledge management on employee performance, with learning organization as an intervening variable. The data collection method in this study used the questionnaire method by taking as many as 178 permanent employees at the Corruption Eradication Commission (KPK) as respondents, especially at the Deputy for Information and Data (INDA). The data analysis used is the Structural Equation Model (SEM) with the Partial Last Square (PLS) equation model. The results of this study indicate that: transformational leadership has no significant effect on employee performance; knowledge management and learning organizations have a significant effect on employee performance; transformational leadership and knowledge management has a significant effect on learning organizations; transformational leadership and knowledge management has a significant effect on employee performance if it is mediated by a learning organization.